Globalisation in Europe: Consequences for the business environment and future patterns in light of Covid-19 - Sergio Inferrera (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2021)
In this paper, I study the consequences of globalisation, as measured by the involvement of firms in GVC, on the business environment. In particular, I focus on concentration and productivity, firstly by estimating robust elasticities and then isolating the exogenous component of the variation in the participation in GVC. To this aim, I exploit the distance between industries in terms of upstreamness and downstreamness along the supply chain. The evidences suggest that involvement in international supply chains is positively related to concentration at the sector level and positively associated with aggregate productivity, an effect that is driven by the firms at the top of the productivity distribution. Finally, I relate these findings to the current pandemic, going beyond the lack of official statistics and estimating GVC participation for 2020 at the country-level through real time world-seaborne trade data, providing evidences on the reabsorption of the Covid shock in several European economies.
urn:nbn:de:gbv:3:2-135781
Keywords: 330; Coronavirus; Globalisierung; Lieferkette; Wirkungsanalyse; EU-Staaten